2018
DOI: 10.4103/ams.ams_1_18
|View full text |Cite
|
Sign up to set email alerts
|

Vascular analysis of radial artery perforator flaps

Abstract: Background:Radial forearm free flap with all its present day modifications is the workhorse of soft tissue reconstruction in head & neck. Although there are several advantages, it requires the sacrifice of a major artery of forearm. There are several modifications of harvesting a forearm flap based on perforator principles. A clear understanding of vascular anatomy of individual perforators relative to its vascular territory & flow characteristics is essential for both flap harvest & design. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…10,12 On the contrary, the mean number of the radial artery perforators was reported as 10 and 8 on the radial and ulnar side, respectively. The average diameters were 1.11 and 0.86 mm on the distal and proximal side, respectively 13 ; these matched the diameter of the ICAPs. Thus, application of SCIP-ICAP compound flap could be versatile for a massive defect from the dorsum of the hand to the proximal upper arm.…”
Section: Discussionsupporting
confidence: 64%
“…10,12 On the contrary, the mean number of the radial artery perforators was reported as 10 and 8 on the radial and ulnar side, respectively. The average diameters were 1.11 and 0.86 mm on the distal and proximal side, respectively 13 ; these matched the diameter of the ICAPs. Thus, application of SCIP-ICAP compound flap could be versatile for a massive defect from the dorsum of the hand to the proximal upper arm.…”
Section: Discussionsupporting
confidence: 64%
“…Anatomical studies have shown that the radial artery also gives appropriate perforators in the proximal part of the forearm. Authors describe their usage for covering defects on the elbow, but no other authors report raising these flaps for covering other flaps' donor sites [11,12]. In our case primarily closure was not possible, therefore, exploration toward radial artery was done to directly visualize skin perforators and appropriate size of perforator propeller flap was harvested, placed into PIAF donor site, closing all wounds primarily.…”
Section: Discussionmentioning
confidence: 88%
“…It is important to know the RA diameter to improve the success rate during transradial coronary interventions. For coronary interventional procedures, using the RA appears to be a preferable option than transfemoral or transbrachial approaches due to easier hemostasis and unimportant veins or nerves around the RA and the presence of perforators [3,4,5,6,7,8,9,10,11,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Updating the knowledge of vascular anatomy in the forearm is useful bringing innovations into the design of the radial forearm flap [7].…”
Section: Introductionmentioning
confidence: 99%